Pe Pengaruh Pendidikan Kesehatan Cuci Tangan 6 Langkah Dengan Metode Demonstrasi Terhadap Sikap Hidup Sehat Siswa Kelas 5 SD Negeri Mokaha 01: penelitian sikap hidup siswa SD Negeri Mokaha 01 - Dhiya Murfidyanto; Yudha Febrianta (JSH: Journal of Sport and Health, 2023)
Washing hands is a trivial thing that must be taught from an early age because children at that age are children who are critical of disease. So a healthy lifestyle needs to be instilled so that it becomes a good habit for students. This research aims to determine the effect of 6-step hand washing health education using the demonstration method on the healthy living attitudes of grade 5 students at SD N Mokaha 01. This research method is quantitative research using a pre-test and post-test design, the population in this study is all students 5th grade at SD N Mokaha 01 with a sampling technique, namely total sampling with a total of 30 respondents. Data analysis used was the Paired Sample T-test statistical test. The pre-test results showed that the majority of students were good, 26 students (86.8%) and the post-test showed that the majority of students were good, 21 students (69.9) with a Sig value = 0.000. The conclusion obtained in this research is that there is an influence of 6-step hand washing health education using the demonstration method on the healthy living attitudes of grade 5 students at SD N Mokaha 01 with a Sig value = 0.000